(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In wireless sensor networks (WSNs), sensors are geographically dispersed and work together to send data to a central base station, such as temperature, sound, pressure, and other environmental variables. The WSN is made up of a large number of nodes, ranging from a few dozen to several thousand, all of which are interconnected through sensors. Clustering is an essential technique in wireless sensor networks for extending the network’s lifespan (WSNs). In this process, sensor nodes are grouped into clusters, and cluster heads (CHs) are elected for each cluster. In this study, we have studied the wireless sensor networks, routing protocols in WSN, clustering, advantages of clustering, design challenges of clustering, optimization-based clustering mechanisms which are concluded that a significant strong method for preserving the energy efficiency of a sensor network is through energy restrictions of sensor hubs and the capabilities of the clustering architecture